Analysis of the influence of product quality and price on customer loyalty at Bonaparte Coffee House in Rappang - Nurbina Nurbina; Pratiwi Ramlan; Wahyuni Saleh (Institute of Computer Science (IOCS), 2024)
This study aims to determine the Influence of Product Quality and Product Price on Bonaparte Coffee House customer loyalty in Rappang. The population in this study is Bonaparte Coffee House Sidenreng Rappang consumers conducted using the Accidental Sampling technique using the Slovin formula, so that 60 consumers were used as respondents. The research method uses correlational quantitative research. The data used is primary data obtained using questionnaires, observations, interviews, and documentation. The data analysis techniques used were multiple linear regression coefficient analysis, determination coefficient, t-test statistical analysis and F-test statistical analysis